Distribution of Subsidized Fertilizer in Karawang Regency - Siti Hamidah; Eka Yulyana; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
Fertilizer is one of the important inputs in increasing the productivity of food crops, so that its existence and utilization has a strategic position. In achieving national food security, the central and regional governments are obliged to ensure the availability of agricultural needs such as fertilizers. One of the policies in the procurement of fertilizers is fertilizer subsidies. Fertilizer subsidies have long been implemented with various policies that follow it, such as policies on fertilizer procurement, distribution of fertilizers and supervision of subsidized fertilizers. In an effort to implement optimal policies, it is necessary to study the existing subsidized fertilizer policies, taking into account the supporting factors and inhibiting factors of the implementation of existing policies based on the needs of the community, especially farmers. Besides that, formulating a more appropriate model in the distribution of subsidized fertilizers.